Muhammad the man & His message - Yasin, Shaykh Khalid; One Islam Publications (N.S.W, Australia : One Islam Productions, 2006)
In this lecture Shaykh Khalid Yasin explains this great man, Muhammad (pbuh), his mission and his message
Title from title screen
Presenter : Shaykh Khalid Yasin
Keywords: Muhammad, -- Prophet, -- d. 632